MATERNITY NURSING CARE MANAGEMENT SERVICE EXCELLENCE FOR MRS. H WITH FIRST TRIMESTER HYPEREMESIS GRAVIDARUM AT SANTI MELIALA CLINIC MEDAN POLONIA SUB-DISTRICT, NORTH SUMATRA PROVINCE YEAR 2025 - Kleng Ate, Marta; Herna Rinayani Manurung; Lisdayanti Simanjuntak; Samuel Waruwu; Toni Rian Rialdi Silaban; Kesya Wulan Anggini Br Situ morang; Wika Marisanulo Telaumbanua, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Hyperemesis gravidarum is a pregnancy complication characterized by persistent, severe nausea and vomiting, which can lead to weight loss of more than 5% of pre-pregnancy weight, dehydration, acid-base imbalance, and hypokalemia. According to 2021 World Health Organization (WHO) data, the incidence of hyperemesis gravidarum reached 12.5% of all pregnancies worldwide, and its prevalence tends to increase to 15%. Data from the Santi Meliala Inpatient Primary Clinic shows an increase in the number of cases from 85 patients in 2023 to 90 patients in 2024. This study aims to implement excellent service-oriented maternity nursing care managemen whot for Mrs. H with first-trimester hyperemesis gravidarum. A case study approach was used in this study, covering the stages of assessment, diagnosis, intervention, implementation, and evaluation of nursing care. The results obtained indicate that Mrs. H's nausea and vomiting symptoms were successfully resolved through the implementation of appropriate interventions and holistic and professional nursing services. By implementing excellent service, the quality of nursing care for patients with hyperemesis gravidarum can be improved, thereby helping to accelerate the recovery process and increase patient satisfaction with healthcare services.(WHO, 2023)( Minister of Health Regulation , 2021)